Implementasi Metode Extreme Programming Pada Perancangan Sistem Administrasi RT Terintegrasi Payment Gateway Midtrans Berbasis Web - Ryan Akbar Ramadhan; Joko Riyanto (CV. Multi Kreasi Media, 2023)
The current population data management system in the RT only uses a master book that is stored in archive form. Contributions still use a manual recording system where officers still come to residents' homes to ask for monthly contributions, so it is still not effective and there are weaknesses to avoid billing. fees for the RT environment. Extreme programming is one of the most widely used agile methods, especially in small-scale application development projects. This is because this method is relatively simple and concise but still applies various agile principles that are considered break through in increasing the efficiency and effectiveness of software development work. succeeded in creating a website-based information system that makes it easier for the heads of neighborhood units and their residents to administer data and pay monthly fees. The citizen service information system also designed the Margorejo resident data input form, making it easier for admins or employees to enter citizen data and also to view citizen data according to their needs. Residents have been able to make payments through the system without having to wait for officers who come to each resident's house.